DRUG IN ADHESIVE TRANSDERMAL SYSTEM OF FUROSEMIDE: IN VITRO IN VIVO EVALUATION - YALLAMALLI, INDIRA MUZIB; MANNAM, REVATHI; YELLAMELLI, RAMJIAMBEDKAR (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of the present work aims to check the effect of penetration enhancers on release kinetics in a novel drug in the adhesive transdermal system of furosemide. Methods: The adhesive systems were evaluated for pharmacotechnical properties and in vitro permeation of the drug through the excised rat epidermis. Among the DURO-TAKs screened for in vitro permeation studies. The results were quantified using RP-HPLC. The optimized drug in the adhesive system was subjected to in vivo kinetic studies using New Zealand male rabbits. The adhesive systems were further evaluated for tack properties and skin irritation studies. Results: DURO-TAK 2510 demonstrated a best permeation profile than DURO-TAK 2852. A combination of penetration enhancers was proved to more be efficient than alone, in the case of F9 (IPM: PG 7.5:2.5) maximum permeation of the drug (314.45±5.97 µg/cm2) was observed by the end of the study with a flux of 9.2052±0.33 μg/cm2/h. The optimized drug in the adhesive system was subjected to in vivo kinetic studies using New Zealand male rabbits. The studies confirmed that controlled release of the drug for a prolonged duration with an extended AUC and MRT decreased Cmax in adhesive systems compared to the oral route, which can provide a promising pharmacological effect the in the DIA system compared to the oral route. Conclusion: The findings in the present study confirmed that drugs in adhesive systems can provide promising results and can enhance both bioavailability and patient compliance with a combination of penetration enhancers in the development of DIA systems.